Low frequency noise measurement of three-axis surface micro-machined silicon capacitive accelerometer - Mohd-Yasin, F.; Nagel, D. J.; Korman, C. E.; Ong, D. S.; Chuah, H. T. (2007)
Low frequency noise measurement of three-axis surface micro-machined silicon capacitive accelerometer